Effect of Giving Red Ginger Oil on WOMAC Scores in Elderly People with Osteoarthritis - Achmad Syukkur; Febrina Secsaria Handini (Babali Publisher, 2023)
Osteoarthritis (OA) is a slowly progressive non-inflammatory disease of the diarthrodial (synovial) joints with increasing incidence age with initial symptoms of joint pain during activity. The pain will slowly get worse, resulting in obstacles to joint movement and affecting the patient's functional abilities. This study aims to identify the effectiveness of giving red ginger oil for pain, joint stiffness and functional abilities. This research will usetime series with research design of Quasi Experiments pre and post test design with the control group. The intervention by administering red ginger oil was carried out once in a day for 7 days. The sampling technique used non equivalent control group design. Evaluation was carried out on the first day, third day, fifth day and seventh day using the WOMAC score. The result of research shows the significance figure tested using the Pillai, Wilk's Lambda, Hotelling and Roy's procedures, shows the significance figure is below 0.05 (ie 0.000), it can be concluded that the total WOMAC score data at pre, day-3, day-5 and day-7 are different significant between the intervention group and the control group. The results of the study showed a decrease in womac scores in the intervention group, so it is hoped that red ginger oil can be used as an alternative therapy for elderly patients with OA.